A technology acceptance model of satellite-based hydrometeorological hazards early warning system in Indonesia: an-extended technology acceptance model - Igif Gimin Prihanto; Hendy Gunawan; Budhi Riyanto; Wiji Prasetio; Sik Sumaedi; Tri Rakhmawati; Nidya Judhi Astrini; Mahmudi (Cogent Business & Management, 2024)
PurposeThis study aims to develop and test a technology acceptance model for a satellite-based hydrometeorology early warning system in Indonesia.Design/methodology/approachThe model was developed by extending TAM, through the inclusion of three additional variables: trust (T), image (I), and information quality (IQ). Thus, the proposed model involves seven variables: Perceived Usefulness (PU), Perceived Ease of Use (PEU), Attitude to Use (AU), Intention to Use (IU), trust (T), image (I), and Information Quality (IQ). For model testing purposes, data were collected from 100 users through a survey conducted in three Indonesian provinces: Central Java, West Kalimantan, and Riau. The analysis consists of measurement model analysis, structural model analysis, and model fit test. The analysis was conducted using partial least squares structural equation modeling (PLS-SEM).FindingsThe model was proven to be fit, valid, and reliable, with all hypotheses being confirmed. In the context of a satellite-based hydrometeorology early warning system, perceived usefulness (PU) positively and significantly influences the attitude to use (AU). Furthermore, perceived usefulness (PU) also has a positive and significant impact on the intention to use (IU). Additionally, perceived usefulness (PU) is shown to be affected by external factors, namely trust (T) and image (I). Perceived ease of use (PEU) is found to have a positive and significant impact on attitude to use (AU). Furthermore, perceived ease of use (PEU) is influenced by external factors specifically image (I) and information quality (IQ). The attitude to use (AU) is found to have a positive and significant effect on the intention to use (IU).Originality/valueAn extended Technology Acceptance Model (TAM) to test the acceptance of disaster early warning system technology is rare, even though the technology is vital.Research limitations/implicationsIn terms of generalization, this study is limited to the acceptance of the satellite-based hydrometeorology early warning system in Indonesia. Future research should apply the model to other contexts to test its applicability and stability.
Keywords: 650; Early warning system; hydrometeorology; Indonesia; partial least squares structural equation modeling; satellite; technology acceptance model